Measurement of Electrical Properties of Sn-Bi-In Alloys - Kumar M.R.; Behera C.K.; Mohan S. (My University, 2025)
The electrical properties of Sn-Bi-In ternary alloys were measured using the four-point probe method along three cross sections of the phase diagram (ratio of tin to bismuth 2:1, 1:1 and 1:2). The current–voltage relationship was measured for all the alloys from 38°C to 90°C. The variation of electrical resistivity with temperature was studied for all the ternary alloys and Pb-Sn binary alloys using the four-point probe method. The resistivity of ternary alloys was compared with Pb-Sn binary alloys. The resistivity of a few of the ternary alloys, 7Sn-3Bi-90In, 5Sn- 5Bi-90In and 3Sn-7Bi-90In, were close to the values of Pb-Sn alloys. © 2019, The Minerals, Metals & Materials Society.